2019
DOI: 10.1002/btpr.2809
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐based surface enhanced Raman spectroscopy devices for detection of organophosphorus pesticides traces

Abstract: The detection of traces of substances by surface‐sensitive techniques such as surface enhanced Raman spectroscopy (SERS) explores the interaction of adsorbed molecules on plasmonic surfaces to improve the limit of detection of analytes. This article is an overview about recent development in SERS substrates applied in the detection of organophosphorus pesticides on plasmonic surfaces (arrays of metal nanoparticles). The morphology, roughness, chemical functionalization degree, and aggregation level of plasmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…10 Technological advances have paved the way for SERS into environmental and food analysis. [11][12][13][14][15] Important progress has been demonstrated in forensic science. 16 The methodology is also increasingly investigated for applications to detect pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…10 Technological advances have paved the way for SERS into environmental and food analysis. [11][12][13][14][15] Important progress has been demonstrated in forensic science. 16 The methodology is also increasingly investigated for applications to detect pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Some pesticides can be directly detected as a SERS-active molecular species. A review article by Dias Soares and De Olivieira reported that phosmet, methyl parathion, malathion, fenthion, methamidophos, glyphosate, and paraoxon, among others, had been detected by SERS [43]. These chemicals belong to the class of organophosphorous pesticides.…”
Section: Introductionmentioning
confidence: 99%